Analysis of TPACK Competence of Elementary School Physical Education Teachers: A Cross-Sectional Study - Saptani, Entan; Rukmana, Anin; Supriyadi, Tedi (Universitas Pendidikan Indonesia, 2024)
One of the obstacles to teaching physical education in the 21st century is the necessity for teachers to integrate technology-based learning. The TPACK framework plays a crucial role in enhancing the quality of instruction in physical education. This study aims to map the TPACK competencies of physical education teachers. A cross-sectional survey design with a quantitative approach was employed, utilizing convenience sampling techniques. The research participants consisted of 14 physical education teachers from North Sumedang in Sumedang Regency. Data were analyzed using descriptive statistics through the SPSS 20 program. The results indicated that the understanding of the Content Knowledge component was 78.57, categorized as sufficient; Pedagogical Knowledge was 83.48, classified as excellent; Technological Knowledge was 73.21, also sufficient; Pedagogical Content Knowledge was 79.64, appropriate; Technological Content Knowledge was 73.21, sufficient; Technological Pedagogical Knowledge was 74.55, appropriate; and Technological Pedagogical and Content Knowledge was 79.17, also appropriate. The application of TPACK in the learning process showed that 78% of teachers have mastered it; similarly, 78% of teachers demonstrated mastery in implementing learning, while 77% of teachers showed proficiency in evaluating learning. Thus, physical education teachers in the North Sumedang sub-district effectively integrate technology, pedagogy, and content in their physical education instruction. This finding underscores the importance of ongoing support and training to enhance teachers' TPACK competencies, ensuring effective technology integration in physical education.